Examining the Impact of Gamification and Customer Experience on Customer Loyalty in E-commerce: Mediating Role of Customer Satisfaction - Alma Dwi Rachmadanty; Aprillia Audiayani Muhtar; Agustina Agustina (Journal of Enterprise and Development (JED), 2025)
Purpose: This study investigates the impact of gamification and customer experience on customer loyalty with customer satisfaction acting as an intervening variable.Method: This study adopts a quantitative research approach, employing a sample of 174 respondents who are users of the Shopee platform in the Cirebon region. The sampling technique utilized is non-probability sampling, chosen to ensure the representativeness of the sample. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships between the variables.Result: The findings indicate a strong and statistically significant influence of gamification and user experience (UX) on customer loyalty. This relationship occurs both directly and indirectly through the mediating role of customer satisfaction. The study highlights the crucial role of customer satisfaction in establishing a connection between gamification, user experience, and customer loyalty.Practical Implications for Economic Growth and Development: The implementation of gamification and UX strategies contributes to economic growth by enhancing customer satisfaction and loyalty. Mechanisms such as rewards and challenge-based interactions foster greater customer engagement and retention, thereby increasing business competitiveness. High customer loyalty not only encourages repeat transactions but also generates positive word-of-mouth, ultimately promoting sustainable growth within the digital economy.